Genome-wide survey of DNA-binding proteins in Arabidopsis thaliana: analysis of distribution and functions - Malhotra, Sony (Oxford University Press, 2013)
The interaction of proteins with their respective DNA targets is known to control many high-fidelity cellular processes. Performing a comprehensive survey of the sequenced genomes for DNA-binding proteins (DBPs) will help in understanding their distribution and the associated functions in a particular genome. Availability of fully sequenced genome of Arabidopsis thaliana enables the review of distribution of DBPs in this model plant genome. We used profiles of both structure and sequence-based DNA-binding families, derived from PDB and PFam databases, to perform the survey. This resulted in 4471 proteins, identified as DNA-binding in Arabidopsis genome, which are distributed across 300 different PFam families. Apart from several plant-specific DNA-binding families, certain RING fingers and leucine zippers also had high representation. Our search protocol helped to assign DNA-binding property to several proteins that were previously marked as unknown, putative or hypothetical in function. The distribution of Arabidopsis genes having a role in plant DNA repair were particularly studied and noted for their functional mapping. The functions observed to be overrepresented in the plant genome harbour DNA-3-methyladenine glycosylase activity, alkylbase DNA N-glycosylase activity and DNA-(apurinic or apyrimidinic site) lyase activity, suggesting their role in specialized functions such as gene regulation and DNA repair.